Ugotavljanje mutacijskih sprememb v variabilnih genih preurejenih genov za težko verigo imunoglobulina pri bolnikih s kronično limfocitno levkemijo - Pajič, Tadej (Zdravniški vestnik, 2008)
Background Mutational status of rearranged immunoglobulin heavy chain variablegenes (IGHV) in leukaemia cells of patients with chronic lymphocytic leukaemia (B-CLL) is important independent prognostic factor. The outcome of patients with leukaemia cells that use an unmutated IGHV gene is inferior to those patients with leukaemia cells that use a mutated IGHV gene. Unmutated VHgenes can be observed in about half of all B-CLL cases. In addition, the VH3-21 gene usage is an unfavourable prognostic marker independent of the IGHVmutational status. The aims of the study were to determine the mutational status and IGHV gene usage in our cohort of patients with B-CLL and compare the results to those published in the literature. Methods 49 B-CLL patients (19 female, 30 male), median age 63 (range from 37 to 88 years) in various Binet stages (39 Binet A, 6 Binet B, 4 Binet C) were included in the study. All the patients were untreated at the time of blood collection. Leukaemia cells were isolated from venous blood samples of patients by the Ficoll density gradient centrifugation. Total cellular RNA was isolated from leukaemia cells and used to the prepare cDNA by reverse transcription. After heteroduplex analysis, clonal PCR products were identified with polyacrylamidegel electrophoresis. The PCR products were sequenced and mutational status was determined by comparing the sequence of the IGHV region of the patient sample to the most homologous germ line V sequence. Sequence that was homologous more than 98% with their corresponding germ line sequence was considered unmutated. Results Unmutated and mutated IGHV mutational statusin our cohort of patients with B-CLL was found in 44.9% and 55.1%, respectively. At the IGH subgroup level, the most frequently used subgroup wasIGHV3 (34.9%), followed by IGHV1 and IGHV4, found in 28.5% and 26.5%, respectively. Subgroup IGHV2 was found out in 2 patients (4.1%). (Abstract truncazed at 2000 characters)
Keywords: genetics; genetika; hematologija; Hematopoetske matične celice; Hematopoietic Stem Cells; limfocitna levkemija; Multiple Myeloma; Multipli mielom; mutacije; potek bolezni; preživetje; Preživetje, analiza; Survival Analysis